Impact of Deep Tillage and Irrigation Regimes on Crop Performance of Maize-Wheat Cropping System in North-West India - Jeevanjot Dhaliwal (Journal of the Indian Society of Soil Science, 2023)
Maize (Zea mays)-wheat (Triticum aestivum) cropping system could be an alternative for the dominating rice-wheat cropping system which is being faced by many challenges in north-west India. A two year field experiment (2016-18) was carried out on a sandy loam soil to study the effects of deep tillage and irrigation regimes on crop performance of maize-wheat. There were two irrigation regimes in main plots (based on irrigation water to pan evaporation ratio) in maize (1.2 and 0.8) and wheat (1.0 and 0.5); and three tillage treatments in subplots viz. (1) conventional tillage in maize followed by conventional tilled wheat (MCTWCT), (2) deep tillage before the sowing of maize during first season followed by conventional tilled wheat (MDT1-WCT) and (3) deep tillage before the sowing of maize during both the seasons followed by conventional tilled wheat (MDT2-WCT). The root growth of maize and wheat crop was higher under deep tilled plots as compared to conventional tilled plots, thereby, resulting in higher grain yield of maize (13%) and wheat (9%) crop. Deep tillage during both the crop seasons (MDT2-WCT) had non-significant impact on the crop growth and grain yield of maize and wheat in comparison to plots with MDT1-WCT tillage practice.